Organoleptic Quality Of Chiken Meatballs Substituted With Tuna Meat (Thunnus Sp) - Para, Ria Enjelina; Tiven, Nafly Comilo; Liur, Isye Jean (Program Studi Di Luar Kampus Utama Universitas Pattimura, 2022)
Chicken meat is an ingredient that contains high animal protein which contributes a lot in meeting protein needs for humans. Meatballs are processed meat that has been mashed and mixed with spices, flour and then formed into small balls and then boiled in hot water. Meatballs are processed meat that has been mashed and mixed with spices, flour and then formed into small balls and then boiled in hot water. This study aims to determine the organoleptic quality of chicken meatballs substituted with tuna meat. The research method used is using a questionnaire as primary data. The variables observed in this study were color, smell, elasticity, texture and taste. The data obtained will be tested with the Test of Homogeneity of Variances and Anova. If there is a difference between treatments, it will be tested further with Duncan's New Multiple Range Test. The results showed that the substitution of chicken meatballs with tuna fish could change the organoleptic quality of the meatballs, namely color, odor, elasticity, texture and taste, but not significantly.